Statistics of Periodicals in the Baltic States: Data Sources and Collections - Bliūdžiuvienė, Nijolė (Knygotyra, 2024)
Publishing is a significant part of the cultural, creative, and economic sectors. Its research, assessment, and forecasting require grounded, reliable, accurate, consistent, and comparable statistical data. Considering the lack of research in periodicals statistics and the relevance of publishing statistics, as well as the fact that in the Baltic countries, publishing statistics data are collected by institutions at the same level, the problem arises whether the national libraries’ applied foundational recommendations and legal documents, as well as data collection methodology, can ensure data validity, reliability, comprehensiveness, and comparability. This article aims to examine and compare the data collection practices of periodical statistics in the Baltic States. The research object includes the legal foundation of publishing statistics in Lithuania, Latvia, and Estonia, as well as the 2022 publishing statistics resources and official statistics data collections. UNESCO recommendations and International Organization for Standardization standards can be considered guidelines for such data collection and accounting. The legal foundation of publishing statistics consists of legal deposit laws, which must ensure the sources of statistical data. Even though publishing statistics data are collected by national libraries and the source of statistical data in all countries is legal deposits, the statistical data collections are not identical. Countries choose which data to collect, what criteria to apply, and in what form to present them. It is important to emphasize that data on the publishing industry are not presented in statistical collections, although their collection guidelines and presentation importance are highlighted in international recommendations and normative documents. Statistical data on electronic periodicals are provided only by Estonia. National libraries in the Baltic States are official statistics compilers, so summarized publishing statistics data are provided to national statistics institutions, opening new technological possibilities for data analysis and integration of new data. The collections of statistical data on newspapers and magazines can only be compared according to a few main criteria, as countries have chosen different statistical data presentation features, the main ones being the varying categorization and periodicity characteristics of newspapers and magazines.
Keywords: periodical statistics; publishing statistics data; publishing statistics; newspaper; magazine; periodical; serial publication; legal deposit; publishing industry